Anti‐nutritional compounds in pulses: Implications and alleviation methods. Issue 2 (18th June 2021) - Kumar, Yogesh; Basu, Santanu; Goswami, Deepika; Devi, Mridula; Shivhare, Uma Shanker; Vishwakarma, Rajesh Kumar
Abstract: Pulses are a rich source of protein and minerals particularly for the vegetarian and vegan population. However, several anti‐nutritional compounds, such as trypsin inhibitor, phenolic compounds, phytates, cyanogenic compounds, lectins and saponins are also found in the legumes. Most of the anti‐nutritional compounds of the pulses are present in the seed coat. Most of these compounds are sensitive to heat and can be substantially reduced by milling, cooking, germination, fermentation and heat processing. This review paper summarizes anti‐nutritional compounds present in different pulses including their fractions, significance and beneficial and adverse effect on human health. The aim of this paper is to enlighten the readers about the anti‐nutritional compounds present in the pulses and possible processing methods to enhance utilization of pulses.